Parents and schools : (Routledge, 1993)
This book considers the new roles for parents, how they effect traditional notions of home-school partnership and the effects on schools. Parents have been given new rights over their children's schooling. They now have to right to choose the school management. These rights and the new roles for parents as customers and managers are intended to make schools more responsive to parental concerns and to improve school quality